Prediction of Dental Anxiety Based on Pain Anxiety and Mental Pain Among People Referred to Dental Clinics in Kermanshah City - Aliakbar Parvizifard; Khatereh Heshmati; Amir Abbas Taheri (Mashhad University of Medical Sciences, 2022)
Introduction: Toothache is one of the most common complaints related to dental services. People may experience high levels of anxiety when visiting a dentist or avoid receiving services. The term dental anxiety is used to describe a specific type of anxiety caused by the dental environment. The present study aimed to investigate the psychological factors affecting dental anxiety.Materials & Methods: The present study was conducted based on a descriptive-cross-sectional design. Participants were selected via convenience sampling. The sample in this study included 328 patients referred to dental clinics in Kermanshah in 2020-2021. The instruments used in this study included the Pain Anxiety Questionnaire (PASS-20), Dental Anxiety Inventory (DAI), and Mental Pain (OMMP). Finally, after data collection, the data were analyzed in SPSS software (version 24) using Pearson correlation and multiple regression analysis.Results: Based on the results of the Pearson correlation coefficient, pain anxiety showed a positive and significant correlation with dental anxiety (r=0.45) and mental pain (r=0.25) (P=0.001). Based on the results of multivariate regression analysis (Enter), pain anxiety (β=0.356) and mental pain (β=0.139) were significant predictors of dental anxiety (P<0.05).Conclusion: As evidenced by the results of the current study, it can be concluded that psychological factors, such as pain anxiety and mental pain, are effective in dental anxiety. Furthermore, a great deal of pain anxiety can increase dental anxiety due to people's distorted perceptions of dental services.